A theory-driven evaluation of an early childhood school readiness programme in an under-served area in the Western Cape Province - Gumpo, Hlalani (Institute for Monitoring and Evaluation, 2018)
Early childhood development, care and education interventions coordinate resources and services that are aimed at stimulating growth for young children. Resource constraints in low and middle-income countries contribute towards a lag in childhood development initiatives compared to high-income countries. This thesis focused on the context of South Africa where the government has a long-term objective of ensuring that all children have access to quality services. However, the attainment of this goal is currently not a financially viable option, and many community-based organisations resort to alternative provisions of early childhood interventions to ensure that poor children are served. This thesis investigated implementation and associated outcomes for the Family in Focus (FiF) programme. This home-based early education programme that is targeted at young children between the ages of 0-6 years, who live in poor and marginalised communities where access and resources for care and stimulation are limited, was the programme of interest. A small sample theory-driven evaluation approach was applied to this programme to assess its viability to alleviate service access issues and produce meaningful outcomes for marginalised children. Evaluation questions were posed and a descriptive research design and a pre-post non-equivalent group quasi-experimental design that compared the results of the FiF programme to a traditional pre-school were utilised. Qualitative descriptions, descriptive statistics (mean and standard deviation) and inferential statistics (t-tests) were used to analyse the results. The FiF programme theory, although not initially clearly defined, was found to be plausible with moderate change expected for the beneficiaries of the programme. The programme, however, had a very low implementation fidelity level of 37.5%, meaning that the programme was not being implemented according to design. This was further associated with poor outcomes for the small sample of children in the FiF programme group utilised. Across the five developmental outcomes of cognitive, language, motor, social and emotional development, outcomes were particularly poor for the first three development domains against South African norms and the comparison group used in the evaluation. Early childhood education home-visiting programmes have the ultimate goal of improving child development outcomes. However, evidence shows that these programmes seem to be more successful in improving parenting skills and caregiver coping, without reaching the former ultimate goal. The comprehensive approach to assessing child development in underserved areas in this evaluation provided a novel overview of the interaction of multiple factors in school readiness in impoverished communities. There is still a lingering question as to the benefits of home visiting programmes that are increasingly being implemented across the country as an alternative provision of early childhood care and education services.